2001
DOI: 10.1002/jnr.1246
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide modulates nicotinic receptor‐dependent Ca2+ signaling in rat chromaffin cells

Abstract: Ceramide, which is an integral component of the sphingomyelin signaling pathway, can attenuate voltage-gated Ca(2+) channel (VGCC) activity in a number of cell types. The aim of the present study was to determine whether ceramide can also modulate VGCC activity, and as a consequence nicotinic receptor-dependent Ca(2+) signaling and catecholamine secretion, in rat adrenal chromaffin cells. Short-term C(6)-ceramide (CER) treatment dose-dependently inhibited nicotine (NIC)-induced peak intracellular Ca(2+) transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In particular, ceramide activation of PKC~was shown to inhibit AKT activity [3] via a possible physical interaction between PKC~and AKT [8]. In regards to the nicotinic acetylcholine receptors, ceramide also was shown to inhibit voltage-gated calcium activity, thus leading to a reduction in the nicotine-induced Ca + signaling and catecholamine secretion in adrenal chromaffin cells [22]. In our study, we found that PKC~expression along with that of PKCh was significantly reduced in PC-12 cells exposed to nicotine for 48 h, suggesting that nicotine may play a role in altering the negative feedback on AKT activity via modulations in PKC~( Table 2 and Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, ceramide activation of PKC~was shown to inhibit AKT activity [3] via a possible physical interaction between PKC~and AKT [8]. In regards to the nicotinic acetylcholine receptors, ceramide also was shown to inhibit voltage-gated calcium activity, thus leading to a reduction in the nicotine-induced Ca + signaling and catecholamine secretion in adrenal chromaffin cells [22]. In our study, we found that PKC~expression along with that of PKCh was significantly reduced in PC-12 cells exposed to nicotine for 48 h, suggesting that nicotine may play a role in altering the negative feedback on AKT activity via modulations in PKC~( Table 2 and Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Mediation of the action of NGF and nicotinic receptors by ceramide via the release of intracellular calcium stores has been reported (Liu et al, 2001; Numakawa et al, 2003). Using a Ca 2+ ‐free bath solution, the fast Ca 2+ ‐chelating agent BAPTA, and Ca 2+ imaging, we found that intracellular Ca 2+ release was necessary for C 6 ‐ceramide‐induced reduction of I Na .…”
Section: Discussionmentioning
confidence: 99%
“…These biological effects of ceramides are associated with the regulation of intracellular enzymes such as protein kinase C (Bourbon et al, 2000), tyrosine kinases, diacylglycerol kinase, and phospholipases (Ruvolo, 2003). It has been reported that ceramides can also act on nerve growth factor (NGF) and nicotinic receptors by the release of intracellular calcium stores in cerebellar neurons and rat chromaffin cells (Liu et al, 2001; Numakawa et al, 2003).…”
mentioning
confidence: 99%
“…It has been reported that C 6 ‐ceramide could stimulate intracellular Ca 2+ release (Liu et al. 2001; Numakawa et al.…”
Section: Discussionmentioning
confidence: 99%
“…1999; Gulbins 2003). It has been reported that C 2 ‐ and C 6 ‐ceramides can also act on nerve growth factor and nicotinic receptors by the release of intracellular Ca 2+ stores in cerebellar neurons and rat chromaffin cells (Liu et al. 2001; Numakawa et al.…”
mentioning
confidence: 99%